The predictive value of urinary albumin-to-creatinine ratio for coronary artery abnormalities in Kawasaki disease - Chen, Ye; Huang, Wanlin; Hou, Miao; Wang, Shuhui; Cao, Lei; Li, Xuan; Lv, Haitao (Frontiers in Pediatrics, 2025)
BackgroundTo explore the application value of the urinary albumin-to-creatinine ratio (UACR) in the predictive of coronary artery (CA) abnormalities in Kawasaki disease (KD) during acute phase.MethodsThis retrospective study included 109 KD patients who were stratified into CA abnormalities and normal CA groups based on echocardiography at one month after KD onset. Clinical, demographic, and laboratory data were analyzed. Urinary microalbumin and urinary creatinine values were collected during the acute phase before high-dose intravenous immunoglobulin (IVIG) therapy, and UACR was calculated.ResultsThe 109 patients consisted of 70 males and 39 females. The orrelation analysis revealed no significant associations between UMA and serum albumin (Alb) (r = −0.073, p = 0.449), or between UACR and serum Alb (r = −0.128, p = 0.186) in KD patients. Among the 109 patients, 23 (21.1%) developed CA abnormalities. The levels of UACR, CRP, ALT and NT-proBNP were significantly elevated in the CA abnormalities group compared to the normal CA group, while serum Alb and prealbumin (PA) were decreased (p < 0.05). Multivariate binary logistic regression analysis identified elevated UACR and reduced serum Alb levels as independent predictors of CA abnormalities (p < 0.05). The optimal cutoff values for UACR and serum Alb were 24.1 mg/g and 37.75 g/L, respectively. Combined UACR and serum Alb, the predictive performance improved, with an area under the curve (AUC) of 0.904 (95% CI: 0.848–0.961), a sensitivity of 91.3%, and a specificity of 81.4%.ConclusionsUACR and serum Alb, assessed during the acute phase of KD, could serve as early biomarkers for CA abnormalities, particularly when analyzed in combination.